Canal-Based Versus Excisional Goniotomy Combined with Phacoemulsification in Mild to Moderate Glaucoma - Agnes Poppy Melina; Kadek Yudia Rustiandini Prasasti; Christina Sherly Damanik (Universitas Airlangga, 2026)
Introduction: Minimally invasive glaucoma surgery (MIGS) is increasingly performed with cataract surgery in patients with mild to moderate glaucoma. The OMNI surgical system and Kahook dual blade (KDB) target the conventional aqueous outflow pathway, yet their comparative effectiveness remains uncertain. Purpose: To compare clinical outcomes of phacoemulsification combined with OMNI versus phacoemulsification combined with KDB in patients with mild to moderate glaucoma. Methods: A systematic review and meta-analysis were conducted according to preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. PubMed, the Cochrane Library, and ScienceDirect were searched for comparative studies evaluating phacoemulsification combined with OMNI versus KDB. The primary outcome was intraocular pressure (IOP)-related efficacy; secondary outcomes were reduction in glaucoma medications and surgical success. Pooled analyses used random-effects models. Results: Five comparative studies were included in the quantitative synthesis. IOP outcomes could not be quantitatively pooled because of inconsistent reporting. Meta-analysis showed no statistically significant difference between OMNI and KDB in reduction of glaucoma medications (mean difference 0.22; 95% confidence interval −0.16 to 0.60) or surgical success (risk ratio 0.98; 95% confidence interval 0.77 to 1.26). Substantial heterogeneity was observed across studies, reflecting differences in study design and outcome definitions. Conclusions: Available comparative evidence did not demonstrate clear superiority of phacoemulsification combined with either OMNI or KDB for glaucoma medication reduction or surgical success in mild to moderate glaucoma. Both procedures remain reasonable adjunctive options during cataract surgery, although interpretation is limited by between-study heterogeneity.